The new record orchids from Wawonii Island - DIAH SULISTIARINI; SITI SUNARTI; HARRY WIRIADINATA (Society for Indonesian Biodiversity, 2007)
Wawonii Island is belonging to Province of South-east Sulawesi, which covers area of about 650 km2. The areas is divided into four forest zones that were protected forests, production forests, limited production forests and social forests. This island was selected as a study site with consideration that this island estimated to have unique flora as same as to Sulawesi Island in general. In addition, so far there is no information about flora in this area. The study was conducted by exploring where the forest area visited, in order to collected and inventoried of plant with special attention to orchid species. Out of this study there are about 80 species of orchid were recorded and three species of them were Anoectochilus cetaceus Bl., Cryptostylis javanica J.J. Sm. and Malaxis koordersii (J.J. Sm.) Bakh. f., identified as new record from Wawonii Island. Those three species according to previous information were admitted as endemic of Java. Although morphologically those three species collected from Wawonii were little bit different to which occurred in Java, but based on the species character they unable to be considered as different species. Consequently since those three the species found in Wawonii Island, those species should be categorized as non endemic of Java.Â© 2007 Jurusan Biologi FMIPA UNS SurakartaKey words: Orchid, new record, Wawonii Island.